Nonlinear shifts in infectious rust disease due to climate change - Joan Dudney (Nature Portfolio, 2021)
Climate change is expected to have major impacts on forest tree diseases. Here the authors analyse long-term data of white pine blister rust in the southern Sierra Nevada, finding evidence of climate change-driven disease range expansion that was mediated by spatially varying host-pathogen-drought interactions.